Investigating the Material Removal Rate Parameters in ECM for Al 5086 Alloy-Reinforced Silicon Carbide/Flyash Hybrid Composites by Using Minitab-18 - Bhiksha Gugulothu; P. S. Satheesh Kumar; Bathula Srinivas; Alapati Ramakrishna; S. Vijayakumar (Advances in Materials Science and Engineering)
This study explained about machining parameters of Al5086/Flyash/Sic hybrid metal matrix composites by the Taguchi technique. Al5086 reinforced in SiC (5–10 wt %) and 8% weight of flyash are retained as constants. The specimens are prepared with the help of the stir casting method. The material removal rate was examined by electrochemical machining under various parameters such as feed rate (0.15–0.30 mm/min), voltage (10–20 V), and electrolyte concentration (20–35 g/litre). Taguchi’s L16 orthogonal array was selected for design of experiments (DOEs), and 16 experimental tests were conducted to examine the effect of the selected machining parameters employed to identify the best optimal levels and also to investigate the effect of electrochemical machining parameters on MRR determined by Minitab-18.